Adsorption of Supranol yellow 4GL from aqueous solution onto activated carbons prepared from seawater algae - Benderdouche, Nouredine; Nemchi, Fadela; Bestani, Benaouda; Belhakem, Mostefa; de Minorval, Louis Charles (Adsorption Science & Technology, 2012)
Adsorbents prepared from seawater algae, viz. green Ulva lactuca (PGA) and brown Systoceira stricta (PBA), by chemical activation were successfully tested for the removal of Supranol Yellow 4GL dye from aqueous solutions. Impregnation in 20% phosphoric acid for 2 h at 170 °C and subsequent air activation at 600 °C for 3 h significantly enhanced the adsorption capacities of both algae relative to their inactivated states. Parameters influencing the adsorption capacity such as contact time, adsorbent dosage, pH and temperature were studied. Similar experiments were carried out with commercially available Merck activated carbon (MAC) for comparative purposes. Adsorption efficiencies were measured at a pH 2 and dosages of 8 g/ and 12 g/ for PGA and PBA, respectively. Batch adsorption experiments resulted in maximum adsorption capacities determined from Langmuir models of up to 263, 93 and 84 mg/g for PGA, PBA and MAC, respectively. BET, FT-IR analyses, iodine number and Methylene Blue index determination were also performed to characterize the prepared adsorbents. The adsorption kinetics were found to comply with the pseudo-second-order model with intra-particle diffusion being the rate-determining step. Thermodynamic analysis confirmed that the adsorption reaction was spontaneous and endothermic. These studies indicate that these seawater algae could be used as low-cost alternatives for the removal of dyes.